Women in politics forms and processes - Sankaran, Kamala 1961- (Har-anand Publications, 1993)
Papers presented at the round tables organized in 1990 and 1991 by various women's research and development organizations and sponsored by the Friedrich Ebert Stiftung, New Delhi.